2022
DOI: 10.1177/00915521221087285
|View full text |Cite
|
Sign up to set email alerts
|

Words of Warning: A Randomized Study of the Impact of Assorted Warning Letters on Academic Probation Students

Abstract: Objective: Superiority experiments supply a critical lens to probe higher education interventions because they can dismantle the collective effect of a program and identify the relative contribution of the core components. However, such lines of inquiry are generally absent in higher education literature. We draw on experimental data to probe the dominant mechanisms of a simple but promising academic probation intervention. Methods: We used a 2 × 2 factorial experiment designed to unpack the effects of an acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Where there is a case of infringement of academic integrity, warning letters have been shown to be effective as a way of correcting behavior for various misdemeanors (Brewer et al, 2019). Studies have however shown variance depending on the age and gender of the recipients (Jones, 1997), the method of message delivery (Moss & Kelcey, 2022) and whether the message is low-threat or high-threat, where sometimes the low-threat letter has been more effective (Shapiro, 2023).…”
Section: Academic Staff Recommendationsmentioning
confidence: 99%
“…Where there is a case of infringement of academic integrity, warning letters have been shown to be effective as a way of correcting behavior for various misdemeanors (Brewer et al, 2019). Studies have however shown variance depending on the age and gender of the recipients (Jones, 1997), the method of message delivery (Moss & Kelcey, 2022) and whether the message is low-threat or high-threat, where sometimes the low-threat letter has been more effective (Shapiro, 2023).…”
Section: Academic Staff Recommendationsmentioning
confidence: 99%